O+ Escape During the Extreme Space Weather Event of 4-10 September 2017 - Schillings,A; Nilsson,H; Slapak,R; Wintoft,P; Yamauchi,M; Wik,M; Dandouras,I; Carr,CM (Space Weather-the International Journal of Research and Applications, 2018)
We have investigated the consequences of extreme space weather on ion outflow from the polar ionosphere by analyzing the solar storm that occurred early September 2017, causing a severe geomagnetic storm. Several Xflares and coronal mass ejections were observed between 4 and 10 September. The first shock—likely associated with a coronal mass ejection—hit the Earth late on 6 September, produced a storm sudden commencement, and began the initial phase of the storm. It was followed by a second shock, approximately 24 hr later, that initiated the main phase and simultaneously the Dst index dropped to Dst = −142 nT and Kp index reached Kp = 8. Using COmposition DIstribution Function data on board Cluster satellite 4, we estimated the ionospheric O+ outflow before and after the second shock. We found an enhancement in the polar cap by a factor of 3 for an unusually high ionospheric O+ outflow (mapped to an ionospheric reference altitude) of 1013 m−2 s−1. We suggest that this high ionospheric O+ outflow is due to a preheating of the ionosphere by the multiple Xflares. Finally, we briefly discuss the space weather consequences on the magnetosphere as a whole and the enhanced O+ outflow in connection with enhanced satellite drag.